2019
DOI: 10.1038/s41598-019-42384-7
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting the interplay between cross-sectional and longitudinal data in Class III malocclusion patients

Abstract: The aim of the study was to investigate how to improve the forecasting of craniofacial unbalance risk during growth among patients affected by Class III malocclusion. To this purpose we used computational methodologies such as Transductive Learning (TL), Boosting (B), and Feature Engineering (FE) instead of the traditional statistical analysis based on Classification trees and logistic models. Such techniques have been applied to cephalometric data from 728 cross-sectional untreated Class III subjects (6–14 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 29 publications
(39 reference statements)
0
9
0
Order By: Relevance
“…:(0123456789) Scientific Reports | (2020) 10:17882 | https://doi.org/10.1038/s41598-020-74488-w www.nature.com/scientificreports/ Beyond differences in ethnicity and gender, skeletal class III malocclusion is strongly linked to genetic components and environmental factors 29 . Current phenotype and genotype studies of this malocclusion [30][31][32][33] have been reported in the literature to develop preventive and therapeutic advances in these patients 34,35 . Recent studies in the field of medicine focus on the search for preventive measures and individualized treatments based on the patient's morphological and genetic components 34,[36][37][38] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…:(0123456789) Scientific Reports | (2020) 10:17882 | https://doi.org/10.1038/s41598-020-74488-w www.nature.com/scientificreports/ Beyond differences in ethnicity and gender, skeletal class III malocclusion is strongly linked to genetic components and environmental factors 29 . Current phenotype and genotype studies of this malocclusion [30][31][32][33] have been reported in the literature to develop preventive and therapeutic advances in these patients 34,35 . Recent studies in the field of medicine focus on the search for preventive measures and individualized treatments based on the patient's morphological and genetic components 34,[36][37][38] .…”
Section: Discussionmentioning
confidence: 99%
“…Current phenotype and genotype studies of this malocclusion [30][31][32][33] have been reported in the literature to develop preventive and therapeutic advances in these patients 34,35 . Recent studies in the field of medicine focus on the search for preventive measures and individualized treatments based on the patient's morphological and genetic components 34,[36][37][38] . However, this will require future research, larger samples, and collaborative multicenter studies 5 to better understand the differences between regions and environmental factors involved.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, clustering refers to the extraction of group latent similarities within data that allow subjects to be grouped into subsections. The clustering assumption states that such subsections of subjects often exhibit the same outcome 70 . In orthodontics, because of the complexity of medical data and heterogeneity of patients, identifying subsections of patients by intuition can be difficult 20 …”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, they do not give a clue about the reasoning that led to deciding the saliency, the relevance or the causal importance of the variables 83,84 . Interestingly, theoretical advancements with methods from statistical physics will also allow determining partial information as estimating longitudinal data from cross‐sectional to create individual prognosis 70 . Humans are brilliant at clinical pattern recognition in dimensions equal to or less than three.…”
Section: Introductionmentioning
confidence: 99%
“…Although in recent years interest concerning treatment of Class III malocclusion has intensified, studies on craniofacial growth of untreated Class III subjects continue to be scarce . To date, investigators have found that Class III malocclusion is the dentoskeletal disharmony with the lowest prevalence in the world; a global range varies from 0% to 26.7% .…”
Section: Introductionmentioning
confidence: 99%